Immunohistochemical Expression of Apoptosis Regulators in Squamous Cell Carcinoma of the Cervix and Their Association with Human Papillomavirus 16/18 Subtypes - Hossein Ayatollahi; Nourieh Sharifi; Mohammad Hadi Sadeghian; Anita Alenabi; Hamid Reza Ghasemian-Moghadam (Balkan Medical Journal, 2014)
Background: Human papillomavirus (HPV) infection is an important aetiological factor in squamous cell carcinoma (SCC) of the cervix. Limited studies have been focused on the differences between carcinogenesis of SCCs with and without HPV infection.